Pengaruh Perputaran Kas, Perputaran Piutang, Perputaran Persediaan dan Rasio Hutang terhadap Tingkat Pengembalian Aset Pada Perusahaan Plastik dan Kemasan yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2017 - Mimelientesa Irman; Abel Iswara (UIR Press, 2019)
The purpose of this study was to analyze the positive effect of Cash Turnover, Receivables Turnover, Inventory Turnover and Debt to Equtity Ratio influence to the profitability of the Plastics & Packaging companies which are listed in Indonesia Stock Exchange (IDX) in 2010-2017 periods. The sample are 9 companies which have been selected by using purposive sampling. The financial statement data has been obtained from the Indonesia Stock Exchange (IDX). The analyze using multiple linear regression analysis with the applicatin instrument of SPSS 19.0. Results showed that simultaneous Cash Turnover, Receivables Turnover, Inventory Turnover and Debt to Equtity Ratio have effects toward Return On Assets. While partialt, it was only Debt to Equtity Ratio have effect on Return On Assets. Cash Turnover, Receivables Turnover and Inventory Turnover didn’t have effect on Return On Assets.